Why are Unemployment and Poverty Still Happening in Borneo Island, Indonesia? - Wahyuningsih, Dian; Yunaningsih, Ani; Priadana, Muhammad Sidik; Darma, Dio Caisar; Purwadi, Purwadi (International Journal of Economics and Financial Issues, 2020)
Efforts to alleviate unemployment and poverty must be done comprehensively, cover various aspects of community life, and be implemented in an integrated manner. The research aims to explain the relationship between variables directly, indirectly, and as a whole, to find out how much influence the minimum wages, education, and inflation rates on unemployment and poverty. The analytical approach through panel analysis based on the panel-common effect in 2015-2019 in 5 regions (West, Central, South, East, and North Borneo Island). Empirical findings state that minimum wages have a negative and significant effect on unemployment, while education has a positive and significant effect on unemployment, and inflation rates have a positive and not significant effect on unemployment. Unemployment has a positive and insignificant effect on poverty. Minimum wages have a negative and insignificant effect on poverty through unemployment, while education and inflation rates are both positive and not significant effects on poverty through unemployment. An increase in the informal sector is needed to reduce unemployment and poverty because the informal sector is the main solution to address this problem. Keywords: Minimum Wages, Education, Inflation Rates, Unemployment, Poverty JEL Classifications: E24, E31, I3 DOI: https://doi.org/10.32479/ijefi.9214